Investigation of the Effect of Aluminum Powder on the Combustion Rate of the Composite - Sayat Yermekuly Kydyrali; Sestager Khusainovich Aknazarov; Alibek Zhumabekovich Mutushev; Juan Maria Gonzalez-Leal; Olga Yuryevna Golovchenko; Sholpan Yesenzholovna Gabdrashova; Marat Iztleuovich Tulepov; Aknur Berdibayevna Seisenova (Crystals, 2023)
This article discusses the combustion of high-energy systems based on the oxidizers ammonium nitrate, potassium nitrate, and a mixture of highly active aluminum grade PAP-1 under conditions of a deficiency or excess oxidant α, under a pressure reduction in the range of 0.1–3 MPa. The objective of this study is to develop materials for the production of high-energy compositions based on oxidizers of ammonium and potassium nitrate, fuel binder, and metallic fuel in the form of aluminum powders ASD-6 and PAP-1. The influence of the amount of excess oxidizer, the amount of metallic fuel, and the grade of aluminum on the rate and completeness of combustion of a high-energy composition have been studied. Experiments were carried out on the studied high-energy systems, depending on the grade of aluminum used and the excess of the oxidizing agent α, and the influence of pressure on the burning rate. The compositions of high-energy compositions based on highly active aluminum with the highest combustion rate of mixtures and combustion completeness were determined.